APPLICATION OF SPLIT ELECTRODE AT ELECTROSLAG REFINING - V. A. Zemtsov; D. A. Meshkov; I. O. Sazonenko (Литьë и металлургия, 2010)
The application of split electrode with different crosssection of components is considered. The advantage of its application as compared to solid ring electrode is shown. There are determined more rational sections of components of split electrode in the article.